The Influence of Interest Rates and Infrastructure on Domestic Investment in Banten Province - Didi Zainuddin Didi za; Anita Ria; Tulus Widjajanto (International Journal of Islamic Business and Management Review, 2023)
This research is aimed at proving whether there is an influencing relationship between the independent variables (Interest Rates) and (Infrastructure) on the dependent variable (Domestic Investment). This research method uses panel data regression analysis by combining two data from time series with cross section. From the test results for individual correlations, it was found that the Interest Rate Variable correlation did not have a partial/individual significant effect on Domestic Investment (PMDN). While the Infrastructure Variable on Domestic Investment (PMDN) has a significant influence partially/individually.Furthermore, joint testing between all independent variables on the dependent variable. (Interest Rates and Infrastructure) together have a significant effect on the dependent variable Domestic Investment (PMDN). Based on this research, it illustrates that low bank interest rates and good infrastructure will be able to encourage increased domestic investment which will ultimately be able to increase GRDP, people's income and people's welfare in Banten province. Therefore the role of the government in terms of improving the quality of infrastructure, especially roads and intervention on interest rates (credit) will greatly assist domestic investors to become entrepreneurs.